(3GdebfY aj QSe GdeUGMa hfbWgGs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s ((3YHO Gddg GdbQjei s)
(3ChdgG (B:s
(3bGd CHh YeQh YKeGf Hf SYjO GdMeO ddg GdPi CcQefG HcJGHg gPG cJGH CPcQ ajg Ef TGA Gddg eG SeYJg ef eTjNJi hQhjJg Yf CFeJi ef eQShe NWhW eUMGa Cgd GdCeUGQ s
(3BNQgG (B:s
(3EP GdedahX Hg ChdkG gh GddGe hGdedahX Hg BNQkG gh GdgeRI HLYdc GdgeRI EHJOGA Ke GdMQcI BNQkG , agPG Hjf , hHGddg GdJhajb Je GdcJGH HMeO Gddg hMSf Yhfg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1809s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdbQGAGJ hGdJLhjOs